2015
DOI: 10.1080/00397911.2015.1045986
|View full text |Cite
|
Sign up to set email alerts
|

Ceric Ammonium Nitrate (CAN)–Catalyzed Multicomponent Reactions: An Efficient Catalyst for Green Organic Synthesis

Abstract: The multicomponent reactions (MCRs) consist of two or more synthetic steps which are carried out without isolation of any intermediate thus reducing time, saving money, energy and raw materials. The development of MCRs in the presence of Ceric Ammonium Nitrate (CAN) is an efficient approach that meets with the requirements of sustainable chemistry. The aim of this review is to highlight the interactive effect of the combined use of MCRs and CAN for the development of new eco-favourable methodologies for synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…Ceric ammonium nitrate (CAN) has been widely applied in organic synthesis, especially as a special single-electron-transfer oxidant . Due to its low toxicity, low cost, safety, air and moisture stability, and ease of handling, it has received increasing attention in recent decades.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ceric ammonium nitrate (CAN) has been widely applied in organic synthesis, especially as a special single-electron-transfer oxidant . Due to its low toxicity, low cost, safety, air and moisture stability, and ease of handling, it has received increasing attention in recent decades.…”
mentioning
confidence: 99%
“…Based on the above-mentioned experimental results and the reported literature, a possible reaction mechanism was proposed (Scheme ). First, the CAN served as a Lewis acid , to promote the formation of the enolized intermediate I , which was easily oxidized by CAN to generate radical II . The resulting radical II either was directly trapped by NO 2 derived from CAN without Cu species or reacted through the possible intermediate IV stabilized by Cu species to afford the desired product 2a .…”
mentioning
confidence: 99%
“…The reaction of aldehydes 1 with dimedone 72 and ammonium acetate or aniline derivatives in the presence of different catalysts and solvents afforded 5 H ‐acridine‐1,8‐dione derivatives 131 (Methods A‐E, Scheme , Table ) …”
Section: Synthesis Of Fused Tricyclic Systemmentioning
confidence: 99%
“…The reaction of aldehydes 1 with dimedone 72 and ammonium acetate or aniline derivatives in the presence of different catalysts and solvents afforded 5H-acridine-1, 8-dione derivatives 131 (Methods A-E, Scheme 73, Table 19). [49,66,[147][148][149] Fekri et al [147] have reported that a one-pot, multicomponent reaction of bis(aldehydes) 132, dimedone 72, and ammonium acetate in the presence of a catalytic amount of nano particle Fe 3 O 4 afforded bis(1-phenyl-1Hpyrazole-4,3-diyl))bis(3,3,6,6-tetramethyl-3,4,6,7,9,10-hexahydroacridine-1,8(2H,5H)-dione derivatives 133 in good yields (Scheme 74).…”
Section: H-acridinesmentioning
confidence: 99%
“…Therefore, synthetic organic chemists focused their attention toward designing reactions by following the principles of green chemistry. [1] This has been achieved by solvent free reaction conditions that eliminates the use of hazardous solvents. [2] Multicomponent reactions are also eco-friendly and efficient green tools as they offer significant advantage such as minimization of waste.…”
Section: Introductionmentioning
confidence: 99%